Phytochemical Screening and the Efficacy of Leaf Extract and Powder of Ageratum conyzoides against Callosobrochus maculatus Fabricius (Coleoptera: Chrysomelidae) on Stored Cowpea Seeds - Obembe Olusola Michael; Kayode Emmanuel Olamide; Adegbola Mary Adeola (Asian Journal of Science, Technology, Engineering, and Art, 2026)
Cowpea weevil, Callosobruchus maculatus, is a major pest of stored grains worldwide and causes substantial postharvest losses in cowpea storage systems. This study evaluated the insecticidal efficacy of leaf powder and ethanol leaf extract of Ageratum conyzoides against C. maculatus based on adult mortality, oviposition, adult emergence, long-term storage protection, seed viability, and phytochemical composition. Fresh leaves of A. conyzoides were air-dried, ground into fine powder, and partially extracted in ethanol at 60 °C for 30 min. The extract was filtered, concentrated using a rotary evaporator, and prepared at concentrations of 2%, 4%, 6%, and 8% (v/w), while leaf powder was tested at dosages of 1, 2, 3, and 4 g (w/w). Phytochemical screening was conducted using standard procedures. The findings show that adult mortality increased with increasing extract concentration, powder dosage, and exposure time. Cowpea seeds treated with A. conyzoides powder at 8 g (w/w) recorded 92.25% mortality within 96 h, whereas 100% mortality was achieved with 8.0% (v/w) ethanol extract within the same exposure period. No oviposition occurred on seeds treated with 8.0% (v/w) extract, and no adult emergence was observed in seeds treated with 4 g (w/w) powder. Extract concentrations of 4%, 6%, and 8% (v/w) completely prevented seed damage during three months of storage, while germination tests after seven days showed 100% germinability in all treated seeds. Phytochemical analysis revealed the presence of alkaloids, glycosides, saponins, anthraquinones, tannins, terpenes, and flavonoids. The study concludes that A. conyzoides leaf powder and ethanol leaf extract are effective botanical treatments for controlling C. maculatus without compromising seed viability. These findings contribute to stored-grain pest management by supporting the use of plant-based insecticides as environmentally safer and potentially cost-effective alternatives to synthetic insecticides.